If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 16 + -1x = 7x + 4 Reorder the terms: 16 + 6x + -1x = 7x + 4 Combine like terms: 6x + -1x = 5x 16 + 5x = 7x + 4 Reorder the terms: 16 + 5x = 4 + 7x Solving 16 + 5x = 4 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 16 + 5x + -7x = 4 + 7x + -7x Combine like terms: 5x + -7x = -2x 16 + -2x = 4 + 7x + -7x Combine like terms: 7x + -7x = 0 16 + -2x = 4 + 0 16 + -2x = 4 Add '-16' to each side of the equation. 16 + -16 + -2x = 4 + -16 Combine like terms: 16 + -16 = 0 0 + -2x = 4 + -16 -2x = 4 + -16 Combine like terms: 4 + -16 = -12 -2x = -12 Divide each side by '-2'. x = 6 Simplifying x = 6
| 3.2= | | 6(-2x-1)=-11(x+1) | | H+6=-22 | | -96-7x=9x+13 | | 3(y-4)=y-6 | | Ay+6=14 | | 6x+3.50=33.20 | | 9-3r=13 | | 6x+1=-92-7x | | 3(2x+1)-5=4(x-3) | | 2t-2y= | | y=x^3+7x^2-245x+35 | | 18=-1.8 | | -52-3=3x+20 | | 2x+15=63-5x | | 6x+5-3x=18+4x | | 1.2=2.5-3b | | 16x^2+16x-1=0 | | 4x^2+6=13 | | C-6=-22 | | x(x+10)+25=0 | | -4(x-5)=12(x+3) | | 6(2x-1)=-11(x+1) | | -2y+3x=2 | | 12x-2y=8 | | 4x+4x=8 | | -9r+5=-28 | | 0.4(y+3)=0.5(y-4) | | 5m+(2m+1)=23 | | 0+50*1-60-60*0+10=10 | | 2+4x=26-x | | 9(m+1)=6m |